Nematodes from the coral reefs in Nha Trang, Khanh Hoa Province, Vietnam: Rhinema bimorpha sp. nov. (Nematoda, Monoposthiidae) - Thu, Nguyen Thi; Phuong, Nguyen Thi Xuan; Long, Phan Ke; Duong, Nguyen Thi Anh; Thu, Nguyen Ngoc Anh; Thanh, Tran Thi Viet; Tu, Nguyen Dinh; Holovachov, Oleksandr (Zootaxa, 2026)
A new species, Rhinema bimorpha sp. nov. is described from the coral reefs in Nha Trang, Vietnam. It is characterized by a coarsely annulated cuticle with 12 longitudinal ridges, of which middorsal and midventral extends only along the anterior part of the body; cephalic sensilla equal to 0.2–0.6 labial region diameters in length; amphideal fovea circular and occupying nearly the entire height of unstriated helmet and 0.4–0.5 of the corresponding body diameter; subventral cuticular ridges in males form bulges about 1.7–2.9 corresponding body diameters anterior to cloaca; spicules arcuate, with poorly developed manubrium and subcylindrical shaft, equal to 1.6–2.1 cloacal body diameters in length; six pairs (one pre-cloacal and five post-cloacal) of posterior setiform copulatory sensilla. The new species differs from R. retrorsum in having relatively larger amphids and shorter helmet (occupying the height of helmet vs. half of the height) and larger number of posterior setiform sensilla in male (one pre-cloacal and 5 post-cloacal pairs vs. 3–4 post-cloacal pairs), and from R. longispicula in having shorter spicules (43–82 µm vs. 120–138 µm) and larger number of posterior setiform sensilla in male (one pre-cloacal and 5 post-cloacal vs. one pre-cloacal and 3 post-cloacal pairs).